(untitled) (Nigerian Journal of Technology, 2008)
The screw or auger conveyor is an important conveyor in agricultural and food processing industries. The classical approach to its analysis and design involve the determination of the type and dimensions of the pitch, capacity, screw housing, clearance, length and diameter, shaft diameter, speed of revolution, filling factor, necessary elevation, and power requirements, in addition to the design of the layout. These are done by a combination of calculation and selection from charts. After these, the torque requirement is checked against maximum allowable torque given in charts, which may require the designer to repeat the process in an iterative manner. This can be frustrating where it is done for different products and where it is necessary to consider alternative designs in order to achieve design optimization. A computer program was developed for the above processes to remove the constraints of the classical approach. The program which is iterative and menu driven, accepts relevant input data (material to be conveyed, required capacity, elevations involved, etc) and does the required calculations, selection and optimization. It then gives the user the required dimensions and parameters of the conveyor. Results of evaluation tests show that the program is efficient in the design process and saves time, especially where alternative designs are required to be produced.